Perceived healthcare quality and contraception utilization among persons recently incarcerated. (November 2022) - Hall, Bianca; Atrio, Jessica; Moore, Shawana; Lorvick, Jennifer; Cropsey, Karen; Ramaswamy, Megha
Abstract: Purpose: Previously incarcerated women have specific gender and physiologic needs that are poorly addressed on community re-entry. The objective of this study is to evaluate the relationship between contraception use and perceived healthcare quality post-incarceration. Additionally, we examine the association between social determinants of health and contraception use post-incarceration. Methods: A secondary analysis of a cross-sectional study of reproductive-aged women with a history of criminal-justice involvement in three cities ( n = 383) was performed. Questions related to demographics, social determinants of health, sexual and reproductive health practices, health services use, and healthcare quality were analyzed. Bivariate analysis and logistic regression examined associations between these variables and contraception utilization among persons recently incarcerated. Results: 35% of the participants used a method to prevent pregnancy. There were no significant differences noted between contraceptive users and non-users in perceived healthcare quality. Participants who were not using a contraceptive method were more likely to lack health insurance and experience food insecurity when compared to contraceptive users. Conclusions: Although there was no difference in perceived healthcare quality between contraceptive users and non-users, significant barriers to contraceptive access on community re-entry exist. More studies are warranted to explore the sexual and reproductive health of previously incarcerated women. Highlights: Equitable contraceptive access is important on community re-entry Social determinants of health significantly impact reproductive healthcare access and autonomy Formerly incarcerated women have nuanced needs and need specialized environments to address them